An Alternative Method for Long-Term Culture of Chicken Embryonic Stem Cell In Vitro - Li Zhang; Yenan Wu; Xiang Li; Shao Wei; Yiming Xing; Zhengxing Lian; Hongbing Han (Stem Cells International)
Chicken embryonic stem cells (cESCs) obtained from stage X embryos provide a novel model for the study of avian embryonic development. A new way to maintain cESCs for a long period in vitro still remains unexplored. We found that the cESCs showed stem cell-like properties in vitro for a long term with the support of DF-1 feeder and basic culture medium supplemented with human basic fibroblast growth factor (hbFGF), mouse stem cell factor (mSCF), and human leukemia inhibitory factor (hLIF). During the long culture period, the cESCs showed typical ES cell morphology and expressed primitive stem cell markers with a relatively stable proliferation rate and high telomerase activity. These cells also exhibited the capability to differentiate into cardiac myocytes, smooth muscle cells, neural cells, osteoblast, and adipocyte in vitro. Chimera chickens were produced by cESCs cultured for 25 passages with this new culture system. The experiments showed that DF-1 was the optimal feeder and hbFGF was an important factor for maintaining the pluripotency of cESCs in vitro.